Twenty-five years of national health IT: exploring strategy, structure, and systems in the English NHS. (28th December 2018) - Price, Colin; Green, William; Suhomlinova, Olga
Abstract: Objective: There is global interest in implementing national information systems to support healthcare, and the National Health Service in England (NHS) has a troubled 25-year history in this sphere. Our objective was to chronicle structural reorganizations within the NHS from 1973 to 2017, alongside concurrent national information technology (IT) strategies, as the basis for developing a conceptual model to aid understanding of the organizational factors involved. Materials and Methods: We undertook an exploratory, retrospective longitudinal case study by reviewing strategic plans, legislation, and health policy documents, and constructed schemata for evolving structure and strategy. Literature on multi-organizational forms, complexity, national-level health IT implementations, and mega-projects was reviewed to identify factors that mapped to the schemata. Guided by strong structuration theory, these factors were superimposed on a simplified structural schema to create the conceptual model. Results: Against a background of frequent NHS reorganizations, there has been a logical and emergent NHS IT strategy focusing progressively on technical and data standards, connectivity, applications, and consolidation. The NHS has a complex and hierarchical multi-organization form in which restructuring may impact a range of intra- and inter-organizational factors. Discussion: NHS-wide IT programs have generally failed to meet expectations, though evaluations have usually overlooked longer-term progress. Realizing a long-term health IT strategy may be impeded by volatility of the implementation environment as organizational structures and relationships change. Key factors influencing the strategy–structure dyad can be superimposed on the tiered NHS structure to facilitate analysis of their impact. Conclusion: Alignment between incremental health IT strategy and dynamic structure is an under-researched area. Lessons from organizational studies and the management of mega-projects may help in understanding some of the ongoing challenges.